Poverty Dynamics and Moderating Effects on Labor Force–Economic Growth in Tanjung Jabung Timur - Asrofin, Asrofin; Putra, Adi; Nurdin, Nurdin; Nurkodri, Moh Sahroni (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: This study aims to analyze the effect of labor force and poverty on economic growth in Tanjung Jabung Timur Regency for the 2016–2025 period, and to examine the role of poverty as a moderating variable. This topic is important because regional economic growth is not always accompanied by a proportional reduction in poverty. Problem Background: The main issue addressed is the relationship between labor, poverty, and economic growth, and whether poverty strengthens or weakens the impact of labor on economic growth. Novelty: The novelty of this study lies in incorporating poverty as a moderating variable in the labor–economic growth nexus at the regional level, which remains relatively underexplored in prior studies. Research Method: This study employs a quantitative approach using time series data from 2016–2025 obtained from official regional statistics. The analytical methods include multiple linear regression and Moderated Regression Analysis (MRA) with an interaction term (X1*X2). Findings/Results: The results indicate that labor has a positive and significant effect on economic growth (β = 0.298; sig. 0.004), while poverty has a negative and significant effect (β = -0.145; sig. 0.045). The interaction term (β = -0.0021; sig. 0.027) reveals that poverty weakens the effect of labor on economic growth. Conclusion: In conclusion, increases in labor force do not optimally promote economic growth without a reduction in poverty levels. The implication is that development policies should simultaneously focus on improving labor quality and reducing poverty.